Faith and power : religion and politics in the Middle East - Lewis, Bernard, 1916-2018 (Oxford University Press, 2010)
"Bernard Lewis is recognized around the globe as one of the leading authorities on Islam. Hailed as "the world's foremost Islamic scholar" (Wall Street Journal ), as "a towering figure among experts on the culture and religion of the Muslim world" (Baltimore Sun ), and as "the doyen of Middle Eastern studies" (New York Times ), Lewis is nothing less than a national treasure, a trusted voice that politicians, journalists, historians, and the general public have all turned to for insight into the Middle East. Now, Lewis has brought together writings on religion and government in the Middle East, so different than in the Western world. The collection includes previously unpublished writings, English originals of articles published before only in foreign languages, and an introduction to the book by Lewis"--Provided by publisher.